An endocrinological emergency masquerading as an overdose. (11th July 2012) - Sinha, Nihal; Rahman, Faisal; Shin, Mirae; Burbridge, Peter
Abstract : Primary adrenocortical insufficiency (Addison's disease) is a potentially life-threatening endocrinological disorder caused by destruction of the adrenal cortex with consequent reduction in glucocorticoid and mineralocorticoid function. Although this is a rare condition, misdiagnosis can result in fatal consequences. Previous case reports have described the neuropsychiatric manifestations of Addison's disease which can result in misdiagnosis. Here the authors describe how a psychiatric history combined with atypical biochemical results can point towards a mistaken diagnosis of poisoning and hence disguise an Addisonian crisis.